(untitled) (Iranian Journal of Kidney Diseases, 2023)
Introduction. Membranous nephropathy (MN) has variable clinical outcomes, ranging from spontaneous remission to slow progression to kidney failure. Since the clinical outcomes of MN have not been studied in a large sample size in Iran, this study was designed to evaluate the outcome of patients diagnosed with MN at Hasheminejad Kidney Center (HKC), Tehran. Methods. In this retrospective cohort study, 1086 patients with a diagnosis of MN who were biopsied between 1998 and 2018 in HKC were evaluated through a review of medical records for baseline clinical and laboratory characteristics at the time of biopsy and through a review of follow-up charts and phone calls for the evaluation of clinical outcomes. Of these patients, 551 could be followed for clinical outcomes. The composite outcome included kidney loss (hemodialysis, transplantation, or death). The effect of demographic, clinical, laboratory, and pathological variables on kidney survival was determined by the Cox-regression model using SPSS-16 software at a significance level of .05. Results. Sex (P < .05), higher weight (P < .05), older age (P < .001), hypertension (P < .001), higher baseline proteinuria and lower glomerular filtration rate (GFR) at the onset of the disease were associated with kidney failure (P < .001). A higher percentage of interstitial fibrosis, tubular atrophy, global sclerosis, and a higher pathological class of membranous nephropathy were significantly associated with disease outcome in the univariate Cox-regression analysis (P < .001). Kidney survival rates at 5, 10, and 15 years were 86%, 74%, and 56%; respectively. Conclusion. Our study suggests that baseline demographic, clinical and laboratory factors affect kidney outcomes. Patients who are considered high-risk based on the criteria listed above may need to be candidates for more aggressive therapy. DOI: 10.52547/ijkd.7373